Barium titanate/epoxy resin composite nanodielectrics as compact capacitive energy storing systems - G. C. Manika; G. C. Psarras (eXPRESS Polymer Letters, 2019)
Barium titanate/epoxy resin composite nanodielectrics were manufactured and their capability to store and harvest energy, upon request under DC conditions, was studied in this work. Morphological characterization in all nanocomposites was performed via scanning electron microscopy images and X-ray diffraction spectra, indicating the successful nanofiller’s integration and dispersion within the polymer matrix. Applied DC voltage level varied from 10 to 240 V and the measurements were performed in the temperature range from 30 to 160 °C. Filler content enhances the energy efficiency of the manufactured systems, reaching the highest value of 58.2% for the 7 phr BaTiO3 nanocomposite. Increase of temperature results in an exponential decay of the coefficient of energy efficiency (neff), indicating leakage currents’ augment. DC and AC conductivity have been determined as a function of temperature for all nanodielectric systems. The temperature dependence of conductivity under DC and AC condition follows an Arrhenius form, which allowed the determination of activation energy in both cases.